Retroperitoneal Solitary Fibrous Tumor: A “Patternless” Tumor - D. Myoteri; D. Dellaportas; C. Nastos; I. Gioti; G. Gkiokas; E. Carvounis; T. Theodosopoulos (Case Reports in Oncological Medicine)
Introduction. Solitary fibrous tumor is a rare type of mesenchymal, spindle-cell tumor reported mostly in the pleura. Retroperitoneal occurrence is rare and histopathological diagnosis is challenging. Case Presentation. A 55-year-old woman with nonspecific abdominal pain was found to have a retroperitoneal/pelvic mass adjacent to the upper rectum. The patient underwent surgical resection in clear margins of this pelvic tumor, entering the total mesenteric excision surgical plane. Final histopathology revealed a solitary fibrous tumor and the case is presented herein. Discussion. Solitary fibrous tumor in the retroperitoneum is rarely found in the literature and to the best of our knowledge less than a hundred cases are described so far. Histopathological diagnosis is mostly based on a “patternless pattern” on microscopic examination, which is a storiform arrangement of spindle cells combined with a “hemangiopericytoma-like appearance” and increased vascularity of the lesion. Surgery is the mainstay of treatment and recurrence rates are generally low.